A Literature Review of Salam Contract for Agricultural Development in Gombe State, Nigeria - Ibrahim Dahiru Idriss; Ikilima Abubakar Sheriff; Adamu Abubakar Muhammad (IAIN Padangsidimpuan, 2022)
Agriculture is essential to a country's economic development as seen in many advanced and developed nations who have valued and viewed agriculture as a catalyst for national prosperity and major source of food security. Bay’ Salam can be directly translated to ‘a forward sale or contract whereby a buyer purchases specific commodities that will be delivered by a seller in a future date which is more relevant to agricultural development. Although little has been accomplished in Nigeria, successive governments have placed a strong emphasis on the need to give the agricultural sector top priority to achieve both local and export food sufficiency. It's interesting to note that Gombe is recognized as one of the Nigerian states that have prioritized food and cash crop production as a vital endeavor that can improve both the state's and the nation's fortunes. However, agriculture must be integrated into modern society through Salam contract as suggested by this research to simplify agricultural endeavors, have a positive economic impact on the lives of farmers and rural communities, and to meet its demands and overcome its obstacles in Gombe state, Nigeria. The work used a qualitative research method that includes interview with relevant people on the subject matter and literature review to gather data. The study suggests that, if adopted, managed, and effectively used, the opportunities provided by Salam contract will strengthen the agricultural sector, lessen the frequent conflicts between farmers and herders, and ensure food security in Gombe State, Nigeria